PENGARUH LITERASI ZAKAT TERHADAP KEPERCAYAAN MUZAKKI PADA NU CARE-LAZISNU CABANG JEPARA - Dimas Ananda; Aan Zainul Anwar (DPPM Universitas Pelita Bangsa, 2023)
Indonesia is the largest Muslim country in the world, but the gap in the potential and realization of zakat is quite high. Whereas zakat is an obligatory worship that must be fulfilled by every Muslim. In addition to the role of amil in managing zakat funds, zakat muzakki literacy is also a factor in the gap in zakat potential. This study aims to determine the effect of zakat literacy on the trust of muzakki at NU Care-Lazisnu Branch Jepara. This study uses quantitative methods, with multiple linear regression. Data were obtained through a questionnaire of nahdliyin (member of Nahdlatul Ulama) who live in Jepara Regency who distributed zakat through NU Care-Lazisnu with a total population of 85,860 people and the number of samples is 100 respondents. The variables of this research are knowledge of zakat in general, knowledge of the obligation to pay zakat, knowledge of 8 asnaf, knowledge of zakat calculation and knowledge of the object of zakat. The results of this study indicate that knowledge of the obligation to pay zakat and knowledge of the 8 asnaf have a positive effect on muzakki's belief in lazisnu, while knowledge of zakat in general, knowledge of zakat calculation, and knowledge of the object of zakat do not have a positive effect on muzakki's belief in lazisnu.